Milestones in autonomous driving and intelligent vehicles - Part 1: control, computing system design, communication, HD map, testing, and human behaviors - Chen, Long; Li, Yuchen; Huang, Chao; Xing, Yang; Tian, Daxin; Li, Li; Hu, Zhongxu; Teng, Siyu; Lv, Chen; Wang, Jinjun; Cao, Dongpu; Zheng, Nanning; et al. (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Interest in autonomous driving (AD) and intelligent vehicles (IVs) is growing at a rapid pace due to the convenience, safety, and economic benefits. Although a number of surveys have reviewed research achievements in this field, they are still limited in specific tasks and lack systematic summaries and research directions in the future. Our work is divided into three independent articles and the first part is a survey of surveys (SoS) for total technologies of AD and IVs that involves the history, summarizes the milestones, and provides the perspectives, ethics, and future research directions. This is the second part (Part 1 for this technical survey) to review the development of control, computing system design, communication, high-definition map (HD map), testing, and human behaviors in IVs. In addition, the third part (Part 2 for this technical survey) is to review the perception and planning sections. The objective of this article is to involve all the sections of AD, summarize the latest technical milestones, and guide abecedarians to quickly understand the development of AD and IVs. Combining the SoS and Part 2, we anticipate that this work will bring novel and diverse insights to researchers and abecedarians, and serve as a bridge between past and future.
Keywords: autonomous driving (AD); communication; computing system design; control; high-definition map (HD map); human behaviors; intelligent vehicles (IVs); perception; planning; survey of surveys (SoS); testing